Self-Directed Learning untuk Membangun Kepuasan dan Kepercayaan Diri Mahasiswa Keperawatan dalam Pembelajaran Keterampilan Pemasangan Infus - Tiana Rachmadita; Auridsa Nihlahani; Sri Wahyuni Badjuka; Tri Johan Agus Agus Yuswanto (FORIKES, 2024)
Nursing students often have difficulty in applying theoretical knowledge into practical skills in the clinical environment. One place for nursing students to learn clinical skills is the clinical skills laboratory. This study aimed to analyze the effect of self-directed learning in the clinical skills laboratory on nursing students' satisfaction and self-confidence during the infusion procedure. The design of this study was a post-test only with control group, involving 92 nursing students, consisting of a control group and a treatment group. The treatment group participated in a simulation based on self-directed learning and the control group participated in traditional teacher-directed learning, with the topic of infusion procedures. Furthermore, student satisfaction and self-confidence were measured using a questionnaire. The results of the analysis showed that there was a difference in student satisfaction between the two groups, with p = 0.006. Meanwhile, for the test of differences in student self-confidence, a p value of 0.005 was obtained, so there was also a difference in student self-confidence between the two groups. The treatment group had higher satisfaction and self-confidence scores. Thus, it can be concluded that self-directed learning is effective in increasing nursing students' satisfaction and self-confidence.Keywords: nursing students; self-directed learning; clinical skills laboratory; satisfaction; self-confidence ABSTRAK Mahasiswa keperawatan sering mengalami kesulitan dalam menerapkan pengetahuan teoretis ke dalam keterampilan praktis di lingkungan klinis. Salah satu tempat bagi mahasiswa keperawatan untuk mempelajari keterampilan klinis adalah clinical skills laboratory. Penelitian ini bertujuan untuk menganalisis pengaruh self-directed learning di clinical skills laboratory terhadap kepuasan dan kepercayaan diri mahasiswa keperawatan selama prosedur pemasangan infus. Rancangan penelitian ini adalah post test only with control group, yang mengikutsertakan 92 mahasiswa keperawatan, yang terdiri atas kelompok kontrol dan kelompok perlakuan. Kelompok perlakuan mengikuti simulasi berbasis self-directed learning dan kelompok kontrol mengikuti traditional teacher-directed learning, dengan topik prosedur pemasangan infus. Selanjutnya dilakukan pengukuran kepuasan dan kepercayaan diri mahasiswa menggunakan kuesioner. Hasil analisis menunjukkan bahwa ada perbedaan kepuasan mahasiswa antara kedua kelompok, dengan p = 0,006. Sementara itu untuk uji perbedaan kepercayaan diri mahasiswa didapatkan nilai p = 0,005, sehingga juga ada perbedaan kepercayaan diri mahasiswa antara kedua kelompok. Kelompok perlakuan memiliki skor kepuasan dan kepercayaan diri yang lebih tinggi. Dengan demikian dapat disimpulkan bahwa self-directed learning efektif untuk meningkatkan kepuasan dan kepercayaan diri mahasiswa keperawatan.Kata kunci: mahasiswa keperawatan; self-directed learning; clinical skills laboratory; kepuasan; kepercayaan diri